alpha 5 beta 1 integrin recycling promotes Arp2/3-independent cancer cell invasion via the formin FHOD3 - Paul NR; Allen JL; Chapman A; Morlan-Mairal M; Zindy E; Jacquemet G; del Ama LF; Ferizovic N; Green DM; Howe JD; Ehler E; Hurlstone A; et al. (ROCKEFELLER UNIV PRESS, 2022)
Invasive migration in 3D extracellular matrix (ECM) is crucial to cancer metastasis, yet little is known of the molecular mechanisms that drive reorganization of the cytoskeleton as cancer cells disseminate in vivo. 2D Rac-driven lamellipodial migration is well understood, but how these features apply to 3D migration is not clear. We find that lamellipodia-like protrusions and retrograde actin flow are indeed observed in cells moving in 3D ECM. However, Rab-coupling protein (RCP)-driven endocytic recycling of alpha 5 beta 1 integrin enhances invasive migration of cancer cells into fibronectin-rich 3D ECM, driven by RhoA and filopodial spike-based protrusions, not lamellipodia. Furthermore, we show that actin spike protrusions are Arp2/3-independent. Dynamic actin spike assembly in cells invading in vitro and in vivo is regulated by Formin homology-2 domain containing 3 (FHOD3), which is activated by RhoA/ROCK, establishing a novel mechanism through which the RCP-alpha 5 beta 1 pathway reprograms the actin cytoskeleton to promote invasive migration and local invasion in vivo.